PINCH is an independent prognostic factor in rectal cancer patients without preoperative radiotherapy - a study in a Swedish rectal cancer trial of preoperative radiotherapy - Holmqvist, Annica (BioMed Central, 2012)
BACKGROUND: The clinical significance between particularly interesting new cysteine-histidine rich protein (PINCH) expression and radiotherapy (RT) in tumours is not known. In this study, the expression of PINCH and its relationship to RT, clinical, pathological and biological factors were studied in rectal cancer patients. METHODS: PINCH expression determined by immunohistochemistry was analysed at the invasive margin and inner tumour area in 137 primary rectal adenocarcinomas (72 cases without RT and 65 cases with RT). PINCH expression in colon fibroblast cell line (CCD-18 Co) was determined by western blot. RESULTS: In patients without RT, strong PINCH expression at the invasive margin of primary tumours was related to worse survival, compared to patients with weak expression, independent of TNM stage and differentiation (P = 0.03). No survival relationship in patients with RT was observed (P = 0.64). Comparing the non-RT with RT subgroup, there was no difference in PINCH expression in primary tumours (invasive margin (P = 0.68)/inner tumour area (P = 0.49). In patients with RT, strong PINCH expression was related to a higher grade of LVD (lymphatic vessel density) (P = 0.01) CONCLUSIONS: PINCH expression at the invasive margin was an independent prognostic factor in patients without RT. RT does not seem to directly affect the PINCH expression.